Analisis Estetika Karya Galih Reza Suseno Yang Berjudul ‘Lunar In Nibiru’ - Nafisa Aqilah; Miftahul Falah; Mertien Roos (Penerbit dan Percetakan, CV. Picmotiv, 2025)
This study discusses aesthetics and creative process in creating a painting, with a case study on the work